Regulating Spin Dynamics of Nitronyl Nitroxide Biradical Lanthanide Complexes through Introducing Different Transition Metals. Issue 7 (22nd February 2021) - Jing, Pei; Xi, Lu; Lu, Jiao; Han, Jing; Huang, Xiaohui; Jin, Chaoyi; Xie, Junfang; Li, Licun
Abstract: Four biradical‐Ln complexes with different transition metal ions, namely [LnM(hfac)5 (NITPh‐PyPzbis)] (M II =Mn II and Ln III =Gd 1, Dy 2 ; M II =Ni II and Ln III =Tb 3, Dy 4 ), were prepared by the reaction of Ln(hfac)3  ⋅ 2H2 O, Mn(hfac)2  ⋅ 2H2 O or Ni(hfac)2  ⋅ 2H2 O with NITPh‐PyPzbis biradical (hfac=hexafluoroacetylacetonate, NITPh‐PyPzbis=5‐(3‐(2‐pyridinyl)‐1 H ‐pyrazol‐1‐yl)‐1, 3‐bis(1'‐oxyl‐3'‐oxido‐ 4', 4', 5', 5'‐tetramethyl‐4, 5‐hydro‐1 H ‐imidazol‐2‐yl)benzene). In complexes 1 –4, the NITPh‐PyPzbis biradical chelates one Ln III ion by means of its aminoxyl moieties and the transition metal ion is introduced through the two N donors from the pyridyl pyrazolyl moiety. Magnetic investigations indicate that complex 4 displays visible maxima in frequency/temperature‐dependent χ′′ signals with two‐step relaxation processes, but complex 2 exhibits no slow magnetization relaxation. The comparison of structure parameters of both Dy complexes indicates that the symmetries of coordination spheres of two Dy ions are D 2d for 2 and C 2v for 4, which thus probably results in different magnetic relaxation behaviors. This work provides new insight for improving properties of Ln‐biradical based SMMs. Abstract : Four new biradical‐3  d –4  f heterometallic complexes have been obtained with Mn(II) and Ni(II) ions. The magnetic behavior of this system could be tuned via introducing different transition‐metal ions. Dy−Ni analogue exhibits two‐step relaxation processes although such behavior is not observed in Dy−Mn analogue.